Current trends in the pragmatics of Spanish - Márquez-Reiter, Rosina; Placencia, María E. (María Elena) (Amsterdam ; Philadelphia, PA : J. Benjamins Pub., 2004)
Current Trends in the Pragmatics of Spanish provides the reader with a representative spectrum of current research in the most dynamic areas of the pragmatics of Spanish. It brings together a collection of academic essays written by well-established as well as emerging voices in Hispanic pragmatics. The essays include applications of pragmatic concepts to sub-fields of (Spanish) linguistics (i.e., pragmatics and grammar; pragmatics and applied linguistics; pragmatics and cross- and inter-cultural communication), studies of 'traditional' topics in pragmatics (i.e., discourse markers, politeness.
Current Trends in the Pragmatics of Spanish; Editorial page; Title page; LCC page; Table of contents; Acknowledgements; Preface; I. The pragmatics of Spanish to date; II. Pragmatics and other disciplines; III. Common topics in pragmatics; IV. Towards an integrated pragmatic theory; Contributors; Index; The Pragmatics & Beyond New Series.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Spanish language -- Discourse analysis; Spanish language -- Spoken Spanish; Pragmatics; Espagnol (Langue) -- Analyse du discours; Espagnol (Langue) -- Espagnol parlé.; Pragmatique; pragmatics; FOREIGN LANGUAGE STUDY -- Spanish; Pragmatics; Spanish language -- Discourse analysis; Spanish language -- Spoken Spanish; Pragmatiek; Spaans; Electronic book